Light weight encryption algorithms for wireless body area networks - Radhika Rani, CH; Sai Jagan, Lakku; Lakshmi Harika, Ch; V. Durga Ravali Amara, V (International Journal of Engineering and Technology, 2018)
Wireless Body Area Network (WBAN) emerges as a major network in today’s world. WBAN comprise of sensors used for applications like health monitoring, military, etc. These sensors are embedded within or out of the body. Security is a major factor in WBAN’s and hence it is essential to provide security for patient’s data. So we study about various encryption algorithms in this paper to provide                 security. The WBAN comprise of body sensors in which the energy resources are limited and since consumption of energy will be more it is essential to go for light weight algorithms to provide security and decrease energy consumption.